Finite Element Analysis of Lightweight Automotive Chassis Structures (Strojniški vestnik – Journal of Mechanical Engineering, 2023)
This paper investigates the structural performance of lightweight automotive chassis using finite element analysis. Different material configurations were evaluated to determine their influence on stiffness, deformation, and impact resistance. The optimized design demonstrates improved structural safety while reducing overall vehicle weight.
Keywords: Automotive engineering; Lightweight structures; Finite element analysis; Structural optimization; Crashworthiness